Identification of drug-related cardiovascular risks: A comprehensive analysis using the FAERS database (2004–2024) - Naishen Qin; Yumei Gan; Jun Ouyang; Jiahui Qin; Yuming Tang; Haili Wu; Shumin Wei; Hui Wang; Jiangnan Huang (PLoS ONE, 2026)
Objective: This study aimed to analyze drug adverse events, identify high-risk medications associated with cardiovascular disease (CVD), and provide evidence for clinical medication safety. Methods: We conducted a retrospective analysis of the FAERS database (2004Q1–2024Q4) using nine CVD-related terms from MedDRA 27.0. Four signal detection methods—PRR, ROR, BCPNN, and MGPS—were employed to identify significant drug—event associations. Results: A total of 1,560,242 CVD-related reports were included. Rofecoxib, phenylpropanolamine and rosiglitazone were strongly associated with CVD, with ROR values of 73.4 (95% CI: 71.16–75.7), 66.8 (95% CI: 23.25–191.94), and 58.69 (95% CI: 57.68–59.76), respectively. These drugs have since been withdrawn or restricted. Subgroup analysis revealed gender and age differences in CVD risk: testosterone related drugs may be associated with cardiovascular disease risk in elderly and male patients, while alendronic acid may be associated with increased cardiovascular risk in female patients. These preliminary associations may stem from mixed indications rather than direct effects of the drugs. Validate and quantify in the real world doxorubicin and other anticancer agents are correlated with cardiotoxicity in children known risks. Additionally, potential associations with previously unreported CVD risks were suggested for paricalcitol, busulfan, gemtuzumab ozogamicin, clofarabine, and clofazimine, which warrant further attention. Conclusion: This study showed that some drugs were significantly associated with CVD, and some of them were newly discovered signals. These findings provide a basis for the generation of new hypotheses about the cardiovascular risk of drugs, but the causal relationship needs to be confirmed by further research.